Isolation and growth-promoting mechanisms of phosphate-solubilizing bacteria from Qinghai-Tibet Plateau in Lespedeza bicolor Turcz - Zhang, Xinru; Liu, Wenjia; Liu, Jiayi; Mei, Xiaoli; Zhang, Jinghua; Wang, Dong; Zhang, Xiaoxia; Zhuang, Jiayao (Frontiers in Microbiology, 2025)
IntroductionThe recovery of slopes in high-altitude areas is often challenging due to insufficient nutrients in the soil, with phosphorus deficiency being a key limiting factor for plant growth. This study aimed to screen highly efficient phosphate-solubilizing bacterial (PSB) strains from undisturbed regions of the Qinghai–Tibet Plateau and investigate their growth-promoting effects on Lespedeza bicolor Turcz, and explore the optimal configuration and mechanism of bacterial strain–plant combinations.MethodsThree strains, Bacillus atrophaeus (Q4), B. megaterium (Q7), and B. megaterium (YG1), were obtained through screening experiments.ResultsThe results of potted plant experiments showed that the inoculation of the three strains increased the biomass of the seedlings to varying degrees (29.9% - 133.5%) and improved the soil nutrient content and enzyme activity. Among these, Q4 and L. bicolor Turcz were a relatively ideal combination, and the Q4 treatment had a better growth-promoting effect (133.5% total biomass increase) compared with the Q7 and YG1 treatments. Compared to the control (CK), inoculation with strain Q4 significantly reduced soil microbial community diversity (p < 0.05) and shifted community composition toward dominance by specific taxa. In addition, environmental factors were positively correlated with the abundance of Q4 bacterial strains, indicating that the inoculation of bacterial agents helped improve the release of soil nutrients. The relative abundance of metabolic genes was significantly higher under the Q4 treatment compared with the CK treatment, with metabolism-related products constituting the largest proportion. The abundance of secondary functional genes, such as those related to the metabolism of cofactors and vitamins, carbohydrate metabolism, and amino acid metabolism, increased under the Q4 treatment compared with the CK treatment.ConclusionThe results suggested that phosphate-solubilizing bacteria could promote the growth of leguminous plants. The study provides a novel approach by leveraging the indirect effects of microbes, that is, increasing soil nutrient content and enzyme activity, to improve the soil environment, which may provide new ideas and methods for ecological restoration in China and similar high-altitude areas in the world.